Estimating branchwood biomass of a tropical hill-forest stand - Ibrahim, Sulong (1995)
Branchwood biomass was estimated as a part of a complete project in estimating the total biomass of a tropical hill forest stand. Thirty sample trees were felled. Tree biomass values were regressed with all the measurable parameters and their transformations. A logarithmic transformation with branch-form quotient gave the best-fit equation. The equations predicted the branchwood biomass of the hill forest stand to be 29.0 t per hectare, which was an overestimate of 1.79%. © 1995.